Post-Transplant Diabetes: Prevalence, Risk, and Management Challenges - Alaaeldin M.K. Bashier; Dileep Kumar; Fakhriya J. Alalawi; Hind Al Nour; Amna Khalifa Al Hadari; Azza Abdulaziz Bin Hussain (Dubai Diabetes and Endocrinology Journal)
The prevalence of diabetes and diabetic nephropathy is increasing, especially in middle eastern countries. Many patients reach end-stage renal disease and either start dialysis or consider preemptive transplantation. Even a higher number of patients develop post-transplant diabetes, which imposes an even higher risk on graft survival and outcomes post-transplantation. Recently, in the UAE, a renal transplant service has been initiated. Because the population is considered at high risk for post-transplant diabetes, we wrote this review article to discuss the prevalence, risk factors, diagnostic criteria, and management, including lifestyle interventions, manipulation of immunosuppressant agents, and suggested algorithms for the use of oral hypoglycemic agents used in the management of post-transplantation diabetes mellitus. We also discussed the specific indications for each of the oral hypoglycemic agents.